Prevention of Body Shaming Behavior through Self-Acceptance Psychoeducation at SMP Negeri 17 Kota Jambi - Periantalo, Jelpa; Nofrianda, Rion; Ulivia, Ayu; Rahim, Benny; Annisa Andriani (Devotion : Jurnal Pengabdian Psikologi, 2025)
This community service activity aims to prevent body shaming behavior among SMP Negeri 17 Jambi City students through an educational approach and intervention involving students directly. Body shaming is the act of demeaning someone based on their physical aspects, which can harm adolescents mental health. The participants of this psychoeducation consisted of 36 students who were randomly selected. The results showed an increase in students' understanding of the adverse effects of body shaming as well as a change in attitude towards a more positive and supportive direction. The educational program implemented effectively raised awareness and strengthened a culture of mutual respect in the school environment. Thus, educational interventions can be an effective solution in reducing body shaming behavior among students.